Peran Guru dalam Menangani Perilaku Bullying di Madrasah Ibtidaiyah Swasta - Mardhiyah, Ulfa Ainul; Rahayu, Mitalis; Nisa, Khoirun (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2025)
The phenomenon of bullying is a serious problem that not only affects physical aspects but also emotional and social aspects that can have long-term impacts. Here, teachers have a fundamental role in preventing and handling bullying at school, namely as guides, mediators or facilitators, and advisors. This study aimed to determine teachers' role in handling the bullying behavior of class II students at MI Al Karomah Bringin Ngawi. The research uses a descriptive qualitative approach. The subjects in this study were teachers and students (perpetrators and victims). The results of the study showed that: 1) the form of bullying behavior occurs at MI Al Karomah Bringin Physical bullying, such as hitting, kicking, and damaging friend's belongings, and verbal bullying in the form of teasing. 2) Factors that cause bullying: the role of the family, where what children receive in the family environment will shape the child's personality; peer factors, the condition of MI Al Karomah Bringin Ngawi's peers who often bully each other, both verbally and non-verbally, which triggers environmental conditions to become increasingly bullying behavior; and social media factors, the mani negative shows watched by children, so that children gradually normalize bullying behavior. 3) The role of teachers in dealing with bullying behavior is as a student mentor; teachers direct students if there is negative student behavior related to this bullying. As mediators/facilitators, teachers can mediate when there is a dispute between students. Teachers are advisors and can provide positive advice to bullies and victims of bullying to achieve a better school atmosphere.